Towards the use of (pseudo) nucleobase substituted amphiphiles as DNA nucleotide mimics and antimicrobial agents. Issue 7 (2nd July 2020) - Ng, Kendrick K. L.; Dimitrovski, Milan; Boles, Jessica E.; Ellaby, Rebecca J.; White, Lisa J.; Hiscock, Jennifer R.
ABSTRACT: Here we present the synthesis of complementary (pseudo) nucleobase appended Supramolecular Self-associating Amphiphilic (SSA) salts and, establish the potential for this molecular construct to produce a new class of DNA inspired synthetic structures/materials. The anionic component of this class of amphiphile contains multiple hydrogen bond donating and accepting functionalities, meaning that these systems can access multiple self-associative hydrogen-bonding modes simultaneously. Herein, we characterise the self-associative properties of these DNA inspired amphiphiles in the solid state, solution state and gas phase. Finally, we investigate the potential of these amphiphilic salts to act as antimicrobial agents against model Gram-positive (methicillin-resistant Staphylococcus aureus – MRSA) and Gram-negative ( Escherichia coli – E. coli ) bacteria. Graphical Abstract: